2011
DOI: 10.5505/tjtes.2011.67503
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of open globe injuries in geriatric patients

Abstract: AMAÇAçık göz küresi yaralanması olan geriatrik hastaların demografik ve etyolojik özelliklerini değerlendirmeyi, prognozu etkileyen faktörleri tespit etmeyi ve güncel literatür eş-liğinde genç nüfusla farklılıkları karşılaştırmayı amaçladık. GEREÇ VE YÖNTEMAçık göz küresi yaralanması nedeniyle 1998-2009 yılları arasında tedavisi ve takibi yapılan 65 yaş üzerinde 30 hastanın dosyaları geriye dönük olarak değerlendirildi. BULGULAROrtalama yaş 73,1 yıl idi. Hastaların %60'ı erkekti ve en fazla sol göz tutulumu va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
1
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 23 publications
1
1
0
Order By: Relevance
“…To the best of our knowledge, this is the first study to determine epidemiological characteristics of older adult patients with ocular and periocular injuries and factors associated with severe ocular and periocular injuries using a citywide registry in the Republic of Korea. Similar to previous studies, the results of the present study showed that injury incidence in males was 2.3-times higher than that in females [2,7,[13][14][15]. The male predominance may be related to their increased participation in outdoor activities [16], and a similar pattern was observed due to the overwhelming frequency of male participation in farm work, mowing and grinding/cutting metal in our study.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…To the best of our knowledge, this is the first study to determine epidemiological characteristics of older adult patients with ocular and periocular injuries and factors associated with severe ocular and periocular injuries using a citywide registry in the Republic of Korea. Similar to previous studies, the results of the present study showed that injury incidence in males was 2.3-times higher than that in females [2,7,[13][14][15]. The male predominance may be related to their increased participation in outdoor activities [16], and a similar pattern was observed due to the overwhelming frequency of male participation in farm work, mowing and grinding/cutting metal in our study.…”
Section: Discussionsupporting
confidence: 90%
“…Falls were also highly associated with open-globe injuries. In Turkey, falls caused only 4% of open-globe injuries among non-older adult patients, but 65% among older adult patients, indicating that falls are the main mechanism of open-globe injury in older adults [14]. Age-related poor balance and mobility associated with deteriorated VA have been known to be one of the risk factors for falls [20].…”
Section: Discussionmentioning
confidence: 99%
“… 28 In other studies, falling was the most common reason. 29 , 30 Since ocular trauma in adults is usually related to working conditions in industry, such as the manufacturing industry, plumbing, mining, and agriculture as well as nonoccupational events such as sports injuries and domestic violence, 31 , 32 greater attentions to safety measures in these situations could be effective in reducing ocular trauma in adults.…”
Section: Discussionmentioning
confidence: 99%